Contamination incidents in the pre-analytical phase of forensic DNA analysis in Austria—Statistics of 17 years. (November 2017) - Pickrahn, Ines; Kreindl, Gabriele; Müller, Eva; Dunkelmann, Bettina; Zahrer, Waltraud; Cemper-Kiesslich, Jan; Neuhuber, F.
Highlights: Contamination statistics of more than 15 years. Contamination incidents caused in the pre-submission phase of forensic DNA analysis. 42% increased detection of contamination using a police elimination database. Abstract: Forensic DNA analyses have become more and more sensitive in the past years. With the ability to generate DNA profiles even from minute amounts of cellular material also the possibility to detect DNA on trace material that originates from persons not linked to the crime event, such as crime scene investigators, increases. The contamination of crime scene samples can lead to false positive results and misinterpretation that can cause deceptive investigations. In this work we continue a study of 2010 that compared the number of detected contamination incidents that were caused in the pre-analytical phase of forensic DNA analysis with the number of crime scene samples analyzed by our laboratory. Within the past 17 years we were able to detect a total of 347 contamination incidents caused by police officers in approximately 46, 000 trace samples to their origin (0.75%). Additionally we demonstrate the usefulness of reference profile databases that contain DNA profiles of police officers to detect contamination incidents of trace material.